Minority ethnicity patient satisfaction and experience: the results of the National Cancer Patient Experience Survey in England - Pinder,RJ; Ferguson,J; Moller,H (BMJ Open, 2016)
OBJECTIVES: The study sought to explore the differential patient satisfaction reported by cancerpatients from ethnic minority backgrounds, examining patient-reported experience of interacting withmedical and nursing staff.SETTING: As a secondary analysis, we collated data collected over two consecutive annual rounds ofthe National Cancer Patient Experience Survey (NCPES) between September 2012 and November2013.PARTICIPANTS: There were 138,878 responses from 155 hospital trusts across the National HealthService in England, representing a response rate of 63.9% based on the total identified cohort ofpatients receiving cancer care over those two years.OUTCOMES: We used the results of the annual survey, that sought to assess overall patientsatisfaction along with patient experience of interacting with clinical nurse specialists, hospital doctorsand ward nurses.RESULTS: Ethnic minority patients reported lower satisfaction and less positive experiences of careoverall. While some of this difference appeared related to demographic and socioeconomic variation,ethnic minority patients remained less positive than those in the White British group after statisticaladjustment. Ethnic minority patients also reported lower confidence in, and less understanding of,health care professionals including clinical nurse specialists, doctors and ward nurses.CONCLUSION: Given the diversity of the British population, as well as the clustering of ethnicminority patients in certain urban areas, a better understanding of the expectations and additionalneeds of ethnic minority patients is required to improve their experience of and satisfaction withcancer care.